Mobile Educational Game of Animal Guess in Android Platform - Permana, Angga Aditya; Perdana, Analekta Tiara; Ramadhan, Yanuardi Eka (Jurnal Informatika, 2022)
The purpose of this research is to create educative digital learning media, easy to understand by children using the waterfall method, educational games guessing animal names with various categories of animals, which can display animal images, animal sounds and animal animations. All designs in the educational game guess the name of the animal